Persuading Voters with Partisan TV News: A Natural Experiment Using Spatial Reception Data - Nicolas Herault; Trevor Kollmann; Russell Thomson (Institute of Labor Economics (IZA), 2024)
We estimate the causal effect of partisan media on voter behavior by exploiting a natural experiment in which Sky News Australia – a conservative 24-hour news channel – became freely available to 8 million people. Using comprehensive national polling-station-level electoral data and broadcast signal strength variation, we implement a continuous treatment difference-in-differences design comparing voting patterns in areas with and without access to the channel before and after its September 2018 free-to-air launch. We find that exposure to partisan media increased the conservative party's lead by 1.5 percentage points in Australia's 2019 federal election. These findings shed light on the role of partisan media in shaping electoral outcomes by influencing swing voters, not just by affecting who turns out to vote.
Keywords: D72; L82; R19; 330; partisan news; elections; spatial economics